Biology, distribution, conservation status and stocking perspective of freshwater crayfish in Greece: An updated review. (18th July 2022) - Alvanou, Maria V.; Papadopoulos, Dimitrios K.; Lattos, Athanasios; Georgoulis, Ioannis; Feidantsis, Konstantinos; Apostolidis, Αpostolos P.; Michaelidis, Basile; Giantsis, Ioannis A.
Abstract: Freshwater crayfish are among the most important aquatic inhabitants in terms of ecosystem integrity retention. Although Astacus astacus and Pontastacus leptodactylus are characterized by the IUCN as vulnerable and least concern, respectively, Greek official data and local authorities report them as highly endangered or threatened at local levels. Therefore, all freshwater crayfishing activities from the main producing areas in Greece have been forbidden for 1 year since August 2021. Since aquaculture in Greece remains primarily focused on marine freshwater fish, freshwater crayfish aquaculture establishment is expected to provide a promising alternative for regional economic development and a solution to unemployment. Under this prism, the present study represents a comprehensive review of the most important features related to biology, distribution, aquaculture methods, economic importance and research progress considering both stocking perspectives and conservation strategies of those two crayfish species. Recent measurements by local authorities for the protection of the freshwater crayfish populations are described and evaluated. Freshwater crayfish aquaculture is expected to be beneficial for Greece, a country that covers all requirements for this sector. The updated information regarding these two species, summarizing the existing literature towards aquaculture conditions, poses suggestions and presents future perspectives on this field.